1993
DOI: 10.1002/bimj.4710350412
|View full text |Cite
|
Sign up to set email alerts
|

Trunk‐Top Relations in a Siberian Pine Forest

Abstract: In this paper we study relations between trunks and tops of pines in natural Siberian forests. By statistical methods we show that the tops tend to deviate in the direction away from the nearest neighbour tree or from a summary of the trees in a given neighbourhood. In an alternative approach we show that the tops deviate into the direction of the empty space near the trunk position defined by the corresponding Voronoi polygon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 4 publications
1
22
0
Order By: Relevance
“…Crown plasticity thus allows for more efficient use of growing space. This process has also been observed by Ishizuka (1984), Gavrikov et al (1993), andLonguetaud et al (2008). More effective exploitation of growing space due to crown plasticity was also shown by a comparison between measured crown projections and simulated circular areas.…”
Section: Spatial Patterns and Canopy Coversupporting
confidence: 78%
See 1 more Smart Citation
“…Crown plasticity thus allows for more efficient use of growing space. This process has also been observed by Ishizuka (1984), Gavrikov et al (1993), andLonguetaud et al (2008). More effective exploitation of growing space due to crown plasticity was also shown by a comparison between measured crown projections and simulated circular areas.…”
Section: Spatial Patterns and Canopy Coversupporting
confidence: 78%
“…An increasing regularity over time has been observed in other forest stands (Gavrikov et al 1993;Oliver and Larson 1996;Longuetaud et al 2008). We also found that crowns were more regularly distributed than stems as a result of the high crown plasticity.…”
Section: Spatial Patterns and Canopy Covermentioning
confidence: 65%
“…The advantage of the spectral approach is that it not only highlights this structure, but that it also provides an associated significance probability. Stoyan and Stoyan (1996) provide a compelling space-domain analysis of these data based on the clear premise that in this forest trees appear in clusters, in common with other natural pine stands (Gavrikov, Grabarnik, and Stoyan, 1993;Penttinen, Stoyan, and Henttonen, 1992). First, they note that attempts to fit a NeymanScott cluster process were not particularly successful.…”
Section: :1 Spectral Point Analysismentioning
confidence: 99%
“…Therefore other tree species can be neglected. In this forest the trees appear in clusters, as also in other natural pine stands, see GAVRIKOV, GRABARNIK, and STOYAN (1993), and PENTTINW, STOYAN, and HENITONEN (1992). Accordingly, Cressie (1991) tried to fit a Neyman-Scott cluster process to the longleaf-pine data.…”
Section: A Case Study: Longleaf-pine Datamentioning
confidence: 94%